ANALYSIS OF STOCK PRICE INDEX VOLATILITY IN INDONESIA USING MACROECONOMIC VARIABLES AND GLOBAL ECONOMIC UNCERTAINTY INDEX - Raihan, Arian Muhammad; Windijarto,; Ceilendra Saksana, Joned (Assets : Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
Stock prices can change within a certain time span can be observed in the volatility of the stock price index. Changes in stock prices can be influenced by a country's macroeconomic conditions and global economic conditions. The macroeconomics observed in this study consisted of interest rates, inflation, exchange rates, and economic growth, while global economic inflation conditions were observed using the Global Economic Policy Uncertainty (GEPU) index. This study aims to examine the effect of macroeconomic variables on the volatility of the stock price index of companies listed on the Indonesia Stock Exchange (IDX) and to change the effect of economic feelings on the volatility of the stock price index of companies listed on the Indonesia Stock Exchange (IDX). A descriptive analysis method was used in this study by utilizing time series data in the time range between the first quarter of 2016 to the fourth quarter of 2021. The results of this study indicate that partially the interest rate has a negative and significant effect on the volatility of the stock price index, while the value of each Global economic exchange and trade partially have a positive and significant effect on stock price index volatility. However, each of the inflation and economic growth variables partially has a positive relationship and does not have a significant effect on the volatility of the stock price index.